Speaking Competence of STMIK STIKOM Indonesia Students Through Video Presentation Project - Kadek Yogi Susana; Gusti Ayu Mahadewi; Gede Diki Prasetya; I Gede Yudi Arsana; Kadek Agus Bisena; Gusti Nyoman Ayu Sukerti (RETORIKA: Jurnal Ilmu Bahasa, 2022)
English at higher education level requires the development of language competence, especially in the development of speaking competence which will be important when it must be applied to communication needs in the industry. To achieve the goal of joining these needs, the use of technology in learning and its evaluation can be one of the determinants of increasing competence. The form of implementation is the assignment of English video presentation which is considered effective in developing competence in the digital and global era as it is today. The stage of creating videos in learning activities can increase student engagement in the lecturing process, increase the effectiveness of the English learning process, stimulate students' creativity and independence, and most importantly foster students' courage to appear and communicate in English. Assessment of the linguistic aspect will help students identify grammatical errors that need to be corrected and improve their verbal skills in English itself. The object of this research is the seventh semester students majoring in Informatics Engineering, STMIK STIKOM Indonesia. The technique of collecting data applied in this research is observation. The data is qualitative data and in the form of English video presentations uploaded by students in the Google Classroom application in the online English class which will be analyzed by using descriptive qualitative methods. The analysis of the linguistic aspect includes pronunciation, grammar, vocabulary, fluency, content, and comprehension. The data obtained will be classified so that students' English competence, especially speaking, can be identified and can be used as the basis for implementing appropriate teaching methods.